A construção dos sentidos e significados do trabalho no Brasil : a influência de fatores demográficos e estruturais - Cibele Ventura Vieira Satuf (2021)
This research focuses the maintenance of work centrality in our society, understanding the social relevance of this category, even under precariousness and flexibilization of working conditions. It argues, therefore, that work is fundamental for the creation of social values. However, the transformations that work and its processes have undergone over the last few years have the potential to change the way individuals relate to the activity. Thus, this research starts from the question: in Brazilian society, what are the shared meanings of work, considering the influence of demographic and structural factors? The investigation is based on the criticism that most research involving the meanings of the work assumes, i.e., that they differ due to occupations and areas of professional activity, focusing on how singular factors influence this process, neglecting broader social aspects. It intends, therefore, to contribute to the scientific literature by expanding its scope, providing elements that offer a sociological interpretation about the influence of sociodemographic and structural factors on shared meanings of work. Based on a literature about the theme under discussion, gender, age, and religious affiliation are listed as demographic characteristics with the potential to influence the formation of their meanings and, as structural factors, the nature of occupational activities and socioeconomic level. The objective of this research was to identify the meanings of the work shared by Brazilians, seeking to examine and understand how these meanings are constructed as well as differ due to the influence of these sociodemographic and structural factors. The investigation adopted a mixed methodological approach, articulating quantitative and qualitative analysis tools, understanding that only such integration would allow a broad understanding of the phenomenon. The quantitative analysis included the use of structural equation modeling to raise some clues about the factors that can influence the attribution of different shared meanings of work. The qualitative stage, performed under the Javier Gil Flores’ interpretive textual analysis, allowed to better understand, through the speech of respondents, how these factors are translated into actions and practices, even unconscious, that leads to the establishment and reproduction of these differentiation. Results showed the maintenance of the centrality of work in our society, reinforcing arguments that contest the theses about the "end of work". In addition, allowed us to verify an intense normativity that attributes to work the role of a social obligation, in line with the values proclaimed by the work ethic highlighted by Max Weber. Our findings also indicated that some demographic characteristics, such as gender and age, as well as structural factors, specifically the nature of the activities and socioeconomic level influenced the paths of these agents on social fields, leading to the formation of different shared meanings about work. They signalized, therefore, reflexes of socialization, which helps guiding, in some way, the positions occupied in social spaces. Such positions influence social perceptions of work and its meanings. But these shared representations about work, are, at the same time, constructed from these positions, and alter them, modifying the dynamics of the social field, transforming reality, as well as the actions of these agents. In this process of relational nature, the role of habitus was evidenced, as well as the function of field/figuration and the distribution of power/capital. These findings allowed us to elucidate that the conformation of shared meanings of work goes through much more complex paths than those based on singular aspects, such as the mere approximation between specific occupations and areas of professional activity. Finally, some limitations of the research were highlighted, as well as guidelines for future investigations.